Frequency of cryptococcal antigenemia in hiv treatment naïve patients with CD4 count below 200/ml - Shaikh, Noorulsaba; Salahuddin, Naseem (Infectious Diseases Journal of Pakistan, 2023)
Background: Cryptococcosis is a dangerous opportunistic fungal infection that poses a significant threat to individuals with advanced HIV/AIDS and compromised cellular immunity. The objective was to determine the frequency of asymptomatic cryptococcal antigenemia in treatment naïve HIV patients. Material and Methods: This cross-sectional study was conducted at The Indus Hospital and Health Network, Karachi from July to December 2022. We included all consecutive HIV patients of age > 18 years, either gender, who were treatment naïve, with CD4 counts ≤200/μL, and did not have any symptoms of cryptococcal infection. Cryptococcal antigen (CrAg) was tested in blood based on the Direct Agglutination test. Results: A total of 100 HIV patients were enrolled. The mean age was 35.12 ± 10.93 years. The majority (78%) of the subjects were males, and 2/3rd were sexually active; exposure to birds was identified in 31% of patients. Most of the patients enrolled belonged to WHO HIV stage 1 (61%), followed by stage 4 (30%). The median CD4 count was 103.5 (IQR: 56.5 – 126.5) /μL. 48 patients had CD4 count between 101 to 200/μL, while 51 patients had CD4 count ≤100/μL. Only 2 patients were found to have CrAg positive making an overall prevalence of 2%. Both patients had a CD4 count ≤ 100/μL (n = 2/51, 3.9%). 30% of patients had other opportunistic co-infections (n = 30). Conclusion: The prevalence of asymptomatic cryptococcosis in the treatment naïve HIV is low in the Pakistani population. A routine CrAg screening can be individualized and avoided in selected patients with CD4 count >100/μL in a resource-limited country like Pakistan. Keywords: AIDS, HIV stages, Asymptomatic, Opportunistic infection.